KEENGGANAN IBU MEMBERIKAN AIR SUSU IBU (ASI) KEPADA ANAK DALAM PERSPEKTIF HUKUM ISLAM - Ezi Ainur Fauziah; Firdaus Firdaus; Azhariah Khalida (UIN Imam Bonjol Padang, 2022)
This research was motivated by the fact that breast milk is the most important and best nutrition for babies from birth, but what happened in Tanjung Senang District was different. there are mothers who are reluctant to give breast milk to their children for various reasons, both acceptable and unacceptable reasons. The formulation of the problem in this study is how the views of Islamic law on the reluctance of a mother to give breast milk (ASI) to children in Tanjung Senang District, Lampung. This type of research is a field research using a descriptive qualitative approach. The approach in this study was intended to identify and describe the reluctance and implementation of breastfeeding by mothers in Tanjung Senang District, Lampung. The technique of collecting data in this research is by interviewing mothers, health workers and religious leaders. Based on the research conducted, it can be concluded that some mothers are reluctant to give breast milk to their children. The reluctance of mothers that occurred in Tanjung Senang District not to breastfeed for various reasons. There is a lack of knowledge, work, breastfeeding is the same as formula milk, lifestyle, breast milk doesn't come out, cannot get support from family and some people's habit of replacing breast milk with other drinks and foods. According to Islamic law, breastfeeding is mandub or recommended. The law of mandub can become mandatory if it harms the soul or the growth of the baby. On this basis, the mother does not give breast milk without a clear reason and contrary to the Shari'a that the mother is seen as lacking in carrying out her religion and obligations because it will make the baby's growth unfulfilled.